Developments in surface contamination and cleaning. Volume six, - Kohli, Rajiv, 1947-; Mittal, K. L., 1945- (William Andrew, 2013)
This work provide a state-of-the-art survey and best practice guidance for scientists and engineers engaged in surface cleaning or handling the consequences of surface contamination.
Keywords: Surfaces (Technology); Surface contamination -- Prevention.; Particles -- Measurement.; Cleaning.; Coatings.; Dust control.; elektronické knihy; electronic books